Taking the Leap from Dyads to Triads: Buyer-Supplier Relationships in Supply Network. - Choi,Thomas; Wu,Zhaohui (Journal of Purchasing and Supply Management, 2009)
A network is made up of nodes and links. The smallest unit that consists of both these network elements is a dyad made up of two nodes (a buyer and a supplier) and the link that connects them (a buyer–supplier relationship). Naturally, the focus of the supply chain management literature has been on this dyad. For instance, a buyer affects a supplier through its supplier evaluation and certificate programs, as well as long-term agreement practices. The relationship between a buyer and its supplier has been characterized as cooperative or adversarial. We have learned a great deal about supply chains through such studies in dyadic context. However, we submit that in a network, a dyad is not the smallest unit of a network. In fact, the smallest unit is a triad, made up of three nodes and the links that connect them. If so, how would this recognition guide us as we move forward to investigate supply chains as a network? What would be its implications to the genre of the literature on buyer–supplier relationships?
Keywords: Supply Chain